INDONESIA LAWYERS CLUB (ILC) SCENE COMMUNICATION IN PRODUCTION MEDIA PERSPECTIVE - Muhamad Afdoli Ramadoni; Andi M Faisal Bakti; Deden Mauli Darajat (Jurnal Komunikasi Islam dan Kehumasan (JKPI), 2023)
Television media had a big role in carrying out the function of providing entertainment, education and of course providing information directly from the scene of the incident with a level of reality that was more complete, lively, original, natural, and even relatively free from the effects of distortion. As shown by the show, Indonesia Lawyers Club could be said as a show that could provide knowledge and understanding to the public about Indonesian law which was discussed broadly and could be explained from various sides and points of view, which included issues of crime, corruption and also existing legal policies. in Indonesia. Based on the background above, the author drawed a major question, namely how was the Indonesian Lawyers Club's communication broadcast in the perspective of production media? This research discussed the Industry that used Media as Business theory in Gill Branston and Roy Stafford's book. Broadcasting Indonesia Lawyers Club had intrinsic strengths in the form of program quality, recognition in the form of awards and achieving high ratings. The broadcast of Indonesia Lawyers Club was able to create a mutually beneficial relationship between Television and political observers, social observers, lawyers and the general public. This broadcast emphasizes that a media production process could actually succeed in presenting ideal broadcasts with all the parties involved in working together, synergizing and Responsible for their duties during the production process